Inspired regional government in Ethiopia to fund dam building for drinking water and its watershed management using CSA options - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The Alliance and its partners inspired the government in Ethiopia to start constructing a drinking water dam for the people of Mekaneselam. Our detailed report investigating the various water harvesting options and suggestions for a suitable location has led to a decision to invest hundreds of millions. We are now working with partners to develop an integrated 'dam catchment management master plan'. When completed the project will benefit the close to 100,000 people of Mekaneselam and its surroundings.